PENGARUH DIGITAL MARKETING DAN BRAND AMBASSADOR DALAM MEMBENTUK BRAND IDENTITY SEBAGAI VARIABEL INTERVENSI TERHADAP PURCHASE INTENTION PADA PRODUK MARKOBAR - Alan Saputro (Jurnal Strategi Pemasaran, 2018)
This research discusses the influence of Digital Marketing, Brand Ambassador to affect Purchase Intention with Brand Identity as the intervening variable. This study includes sample of 100 people who are the followers of Instagram account of MARKOBAR. This research is examining variables including Digital Marketing as first independent variable (X 1), with its indicators consisting Interactive, Incentive, Site Design, Cost. The second independent variable is Brand Ambassador (X 2), with the indicators of Visibility, Credibility, Attraction, Power. Brand Identity as the intervention variable (Y1), with indicators of Brand as Product, Brand as Organization, Brand as Person, Brand as Symbol. The dependent variable of Purchase Intention (Z1), with its indicators consisting Transactional Intention, Referencial Intention, Preferencial Intention, Explorative Intention. The results showed that the value of T-statistics of Digital relationship Marketing and Brand Identity relation of 2.532. A value of the T-statistic of Brand Ambassador and Brand Identity relation of 2.76. A value of the T-statistic of Brand Identity an Purchase Intention relation of 47.446.